2014
DOI: 10.3390/d6040633
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Segregation and Genomic Hybridization Patterns Support an Allotetraploid Structure and Disomic Inheritance for Salix Species

Abstract: Abstract:The Salix alba L. (white willow)-Salix fragilis L. (crack willow) complex includes closely related polyploid species, mainly tetraploid (2n = 4x = 76), which are dioecious and hence obligate allogamous. Because little is known about the genome constitution and chromosome behavior of these pure willow trees, genetic analysis of their naturally occurring interspecific polyploid hybrids is still very difficult. A two-way pseudo-testcross strategy was exploited using single-dose AFLP markers in order to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 27 publications
1
21
0
Order By: Relevance
“…Although some studies are published about tetraploid species in subgenus Salix s.l. (Triest et al 2000; Triest 2001; Barcaccia et al 2014) no molecular studies existed so far on the origin of polyploid species of the Chamaetia/Vetrix clade. In this study we included seven polyploids from Europe with different ploidy levels to test the suitability of RAD sequencing data for polyploids and to study different scenarios of their evolutionary origin.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although some studies are published about tetraploid species in subgenus Salix s.l. (Triest et al 2000; Triest 2001; Barcaccia et al 2014) no molecular studies existed so far on the origin of polyploid species of the Chamaetia/Vetrix clade. In this study we included seven polyploids from Europe with different ploidy levels to test the suitability of RAD sequencing data for polyploids and to study different scenarios of their evolutionary origin.…”
Section: Discussionmentioning
confidence: 99%
“…An analytical toolkit for the discrimination of polyploid willows has been established, based on the combination of SSR markers and flow cytometry, but was only used to detect the ploidy level for breeding purposes (Guo et al 2016). In subgenus Salix , the tetraploid S. alba – S. fragilis complex has been analyzed with AFLP markers and revealed an allotetraploid nature of the species (Barcaccia et al 2014), but in the Chamaetia/Vetrix clade the polyploid species have never been analyzed with molecular markers.…”
Section: Introductionmentioning
confidence: 99%
“…disomic inheritance; Barcaccia et al . ), tetraploid C. stoebe shows tetrasomic inheritance of microsatellite alleles (Rosche et al . ).…”
Section: Methodsmentioning
confidence: 99%
“…Although allopolyploidy may lead to the independent segregations of the two parental genomes (i.e. disomic inheritance; Barcaccia et al 2014), tetraploid C. stoebe shows tetrasomic inheritance of microsatellite alleles (Rosche et al 2016a).…”
Section: T H E S T U D Y S Y S T E M C E N T a U R E A S T O E B E S Lmentioning
confidence: 99%
“…It has been suggested that this might be a consequence of the allotetraploid nature of the genomes of S. alba and S. fragilis, with the two species sharing one common or two highly related diploid ancestor species, but differentiated from each other by the genomic contributions of divergent second diploid ancestor species (Barcaccia et al 2014). The allotetraploid iForest 10: 422-429 426 Rungis genomes of both species, may suggest disomic segregation of genetic loci.…”
Section: Discussionmentioning
confidence: 99%